Enhancing Bakery Business Through Accounting Implementation and Digital Marketing: A Community Service Approach - Mawardi, Rizal; Yatna, Chicilia Nova; Saraswati, Laras Rayi; Salya, Ratih Cucu; Septian, Wahyu Eka (Dinasti Publisher, 2025)
This community service program focuses on strengthening the capacity of Rose Sari Bakery, a small and medium enterprise (SME) located in Bogor, Indonesia. The bakery specializes in producing contemporary wet and dry cakes with premium ingredients and exclusive packaging but faces challenges in production, financial recording, and marketing. The research object is Rose Sari Bakery, a local bakery business in Bantarjati, Bogor. The objectives include improving production capacity through equipment procurement, enhancing financial management capabilities through simple accounting training, and developing digital marketing strategies via Instagram and TikTok platforms. The methodology employed includes observation and needs identification, equipment procurement and training, simple financial recording training, digital marketing strategy enhancement, and evaluation monitoring. The results demonstrate significant improvements in production capacity, implementation of simple accounting systems including cash flow reports and monthly profit-loss statements, market expansion through social media platforms with increased followers and orders from outside Bogor, and anticipated revenue growth. The program successfully contributed to strengthening local SME competitiveness through integrated approaches combining production enhancement, financial management, and digital marketing strategies.